Reprodução socioespacial do campesinato no alto sertão sergipano através do Programa Nacional de Alimentação Escolar - PNAE - Rocha, Mário Artur Barbosa da (2019)
Our study had as an object of research the Programa Nacional de Alimentação Escolar – PNAE (National School Feeding Program), established by the Ordinary Law 11.947/2009, whose article 14 says that at least 30% of the school meal resources, passed on by the National Fund of Education Development of -NFED to the executing entities of the program should be destined to the purchase of food of the agriculture family sector. The issue is to investigate the relationship of the peasants organized by COOPAC - Cooperativa de Produção Agroindustrial e Comercialização do Estado de Sergipe no Alto Sertão Sergipano (Agro-industrial of Production and Commercialization Co-operative in the state of Sergipe in the High Backlands of Sergipe - AIPCCOO), with the institutional market established by NSFP, as well as the evolution of compliance with that law in the state of Sergipe between 2011-2015. These subjects are seated in “Jacaré-Curituba” settlement project, located in “Poço Redondo” District. This area calls attention because of the magnificent irrigation infrastructure that was implemented, the vastness of land and families benefiting from agrarian reform, as well as presenting lots of contradictions that emerge before the investments. The general objective of this research is to investigate the relationship between peasantry and public policies that aim the commercialization of their products, in particular the Programa Nacional de Alimentação Escolar - PNAE (National School Feeding Program) in backlands of Sergipe territory, specifically with the peasants organized in the Cooperativa de Produção Agroindustrial e Comercialização do Estado de Sergipe (COOPAC). Our methodology was based on a review of the literature in relation to the milestone in the global Government in relation to the fight against hunger and Misery (FAO, 1973; 1974; 2017), setting these policies according to the national and local scales. To figure out the reality through socio-spatial processes we consider that it is important to bring to our study the concepts of social space (Lefébvre, 1976), the territorialization of money sources with (OLIVEIRA, 2007), the concept of peasantry (Shanin, 2008) and Unstained The keys of peasant exploration in the sphere of capitalist circulation with (VERGÉS, 2011). The review of the legal framework establishing the NSFP within a historical context that was carried out mainly through the studies of (PEIXINHO, 2011). The field research took place in the “Jacaré-Curituba” settlement, where the headquarters of the AIPCCOO are located and where the interviewed individuals live. Fifteen People were interviewed among men and women. The interviews were conducted between the months of September and October of 2018.